Efektivitas Pemberian Tepung Cacing Sutra (Tubifex Sp) dalam Pakan Terhadap Performa dan Kelangsungan Hidup Benih Ikan Komet (Carassius auratus) - Wahyu Saputro; Syahrizal Syahrizal; Muarofah Ghofur (Jurnal Akuakultur Sungai dan Danau, 2022)
Comet goldfish (Carassius auratus) is a type of freshwater ornamental fish that is popular among the public and has the main advantage of having lots of color variations. The use of fish meal is the biggest obstacle causing the high price of feed and affecting the production of comet fish. The new alternative material to replace fish meal is silk worm flour (Tubifex sp). The aim of this study was to determine the effectiveness of feeding silkworm meal on the performance and survival of comet fish (C. auratus) fry. This research was carried out in February-March 2021 at Perum Yeyes Lestari, Kenali Besar Village, Alam Barajo District, Jambi City for 40 days. The experimental design used in this study was a completely randomized design with 4 treatments and 3 replications, the treatments included 15% silk worm flour (A), 20% silk worm flour (B), 25% silk worm flour (C) 30% silk worm flour (D). The test fish used were comet fish measuring 3-5 cm as many as 120 fish. The results showed that temperature had an effect on survival, absolute weight growth and feed conversion. The color of comet fish for all treatments at the beginning of the study ranged from 3.90-4.43 (golden yellow), while at the end of the study there was a color change that ranged from -2.14-2.83 (dark red). The highest SR was found in treatment A of 86.67% followed by treatment B 70.00% and treatment D 56.67%. The highest PBM value was found in treatment C of 3.26 g. The best FCR value was found in treatment C of 3.56. The results of the analysis of water quality showed that the condition of the culture media was still quite feasible for the maintenance of comet fish in the aquarium container.